EFEKTIVITAS PROGRAM LABORATORIUM BISNIS SANTRI DI PONDOK PESANTREN ANWARUL HUDA MALANG - Muhammad Syifa Zam Zami; Anggraeni, Ika Khusnia (Islamic Economics and finance in Focus, 2023)
The development of information and communication technology in the era of globalization has made Islamic boarding schools experience a paradigm shift from an institution that only focuses on deepening religious knowledge, but also becomes an institution for developing economic potential. One Islamic Boarding School already has a program to expand its economic potential is the Anwarul Huda Malang Islamic Boarding School. This research is here to reveal the extent to which the effectiveness of the students' economic empowerment program, especially the "Laboratorium Bisnis Santri," in fostering the entrepreneurial spirit of students at Pondok Pesantren Anwarul Huda Malang. This study used a mixed method with the CIPP model evaluation approach. Data in the study were collected using questionnaires, interviews, documentation, and observation. Data were analyzed using z-scores and then verified into the Glickman quadrant prototype. The results of this study indicate the effectiveness of the "Laboratorium Bisnis Santri" program at Anwarul Huda Islamic Boarding School Malang is in the Glickman III quadrant with details of the Context variable obtaining a negative frequency (-), a negative frequency Input variable (-), a positive Frequency Process variable (+), and Product variable positive frequency (+). Based on the study results, it can be concluded that the "Laboratorium Bisnis Santri" program is in the less effective category.